2022
DOI: 10.1007/s10935-022-00687-y
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Opium Abuse with Mortality Amongst Hospitalized COVID-19 Patients in Iranian Population

Abstract: Opioid abuse is a serious problem in the society. Since the first months of COVID-19 pandemic, several myths, rumors and misconceptions have been spread about the benefits of opium consumption for COVID-19 outcome. In addition, data are limited on the relationship between opium abuse and COVID-19 mortality amongst hospitalized COVID-19 patients. In this historical cohort study, we assessed the risks of several variables for mortality amongst all hospitalized COVID-19 patients from the beginning of COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It’s crucial to acknowledge that, in our study, while these trends were observed, they did not attain statistical significance. A prior study demonstrated a noteworthy association between opium consumption and mortality in hospitalized COVID-19 patients (relative risk, 1.173) [ 22 ]. Additionally, earlier investigations highlighted notable variations in cytokine levels among opium users, with lower levels of interleukin (IL)-4 and interferon gamma, and higher levels of IL-6 and transforming growth factor-beta compared to controls [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It’s crucial to acknowledge that, in our study, while these trends were observed, they did not attain statistical significance. A prior study demonstrated a noteworthy association between opium consumption and mortality in hospitalized COVID-19 patients (relative risk, 1.173) [ 22 ]. Additionally, earlier investigations highlighted notable variations in cytokine levels among opium users, with lower levels of interleukin (IL)-4 and interferon gamma, and higher levels of IL-6 and transforming growth factor-beta compared to controls [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The onset of COVID-19, along with disruptions in healthcare and social safety nets, compounded by social and economic stressors, intensified the opioid epidemic [ 18 19 20 21 ]. Recognizing factors associated with COVID-19 mortality is pivotal for risk reduction and appropriate interventions [ 22 ]. Hence, comprehensive studies are essential to elucidate the relationship between opium user and mortality in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, opioid consumption increased from 19.79 DHD (defined daily dose/1000 inhabitants per day) in 2019 to 20.88 DHD in 2021 [20], whereas nonopioid analgesic consumption has risen from 32.90 DHD in 2019 to 40.05 DHD in 2021 [21] according to data reported by the Spanish Agency of Medicines and Health Products. An uncontrolled increase in opioid consumption could lead to opium abuse, which has been associated with higher mortality in hospitalized COVID-19 patients [22].…”
Section: Introductionmentioning
confidence: 99%